Komparasi Infiltrasi Antara Area Greenbelt dan Area Terbuka di Kawasan Industri PT Semen Padang - Hendriko, Gilang; Andayono, Totoh (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to compare soil infiltration rates between greenbelt areas and open areas within the PT Semen Padang industrial complex. The study was conducted within the PT Semen Padang industrial complex, focusing on two locations: the greenbelt area and the open area. Measurement points were selected using a purposive sampling method adapted to field conditions. Soil infiltration rates were measured using the double-ring infiltrometer method, and the data obtained were analyzed using the Horton model to describe the soil infiltration patterns. The results showed that soil infiltration rates in the greenbelt area were consistently higher than those in the open area throughout the observation period. At the start of the measurement (t₂), the infiltration rate in the greenbelt area was very high, for example, reaching 144 cm/h at point T1 and 414 cm/h at point T8, whereas in the open area it was only 12 cm/h at T1 and 9 cm/h at T8. As time progressed, the infiltration rate in both areas decreased until reaching a constant value. At the 120th minute, the infiltration rate in the greenbelt area stabilized at a relatively higher value, such as 48.3 cm/h at T1, while in the open area it stabilized at a much lower value, namely 3.6 cm/h at T1. These findings indicate that the greenbelt area has a better initial infiltration capacity (f₀) and constant infiltration rate (f????) compared to the open area.